History of the Formation of the Rule of Law and Civil Society in the Republic of Uzbekistan - Ruziyev Dostonbek Rustam o‘g‘li (Indonesian Journal Publisher, 2026)
Research Purpose: This study aims to analyze the historical stages of the formation of the rule of law and civil society in the Republic of Uzbekistan. It focuses on identifying key factors influencing this evolution and evaluating the outcomes of constitutional and legal reforms aimed at strengthening democratic values. The research employs a comprehensive analysis of legal, political, and social dimensions to understand how the concepts of the rule of law and civil society have evolved. It examines the interrelation between state institutions and independent social organizations, focusing on legislative initiatives and institutional transformations since the country's independence. The findings indicate that the 1992 Constitution created the primary foundation for a legal state by guaranteeing sovereignty and the separation of powers. Over the years, reforms have strengthened judicial independence and expanded the role of the parliament and civil society institutions. Recent reforms starting in 2017 have further liberalized the judicial system, while the 2023 Constitution has specifically bolstered the role of citizens' self-government bodies, known as neighborhoods. The formation of the rule of law and civil society in Uzbekistan is a complex and gradual process shaped by socio-economic and political transformations. While significant progress has been made in establishing a legal framework, further advancement depends on consistent reforms, the consolidation of civic values, and effective interaction between the state and its citizens.